DARI KRITIK MENJADI PANIK: ANALISIS NARASI KONTEN INFLUENCER TENTANG PONDOK PESANTREN TRADISIONAL - Abiano Al Affan (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2026)
Criticism on social media toward traditional pondok pesantren has the potential to influence public opinion, particularly when voiced by influencers with large followers. This study aims to analyze the narrative construction presented in contents of two influencers, Guru Gembul and Herri Pras, who criticize traditional pondok pesantren. Research employs qualitative approach using narrative analysis of YouTube video contents produced by both influencers throughout 2025. Analysis focuses on narrative structure, narrative functions and characters, narrator positioning, and interpretation based on Stanley Cohen’s Moral Panic Theory. Findings reveal that the narratives constructed by both influencers follow a pattern of equilibrium, disruption, awareness of disruption, and attempts at restoration. Traditional pondok pesantren are represented as sources of disruption to what are considered ideal Islamic values through issues such as feudalism, anticriticism culture, moral deviation, and decline of Islamic education. Within this narrative structure, pesantren figures are positioned as folk devils or moral threats, while influencers position themselves as parties who awaken public awareness. Furthermore, as dramatic narrators, influencers construct narratives that tend to be subjective, emotional, and prone to negative generalizations about traditional pesantren. This study demonstrates that social media has significant potential to shape public opinion regarding religious institutions, while also creating stigma, polarization, and moral panic when information is not conveyed in a balanced and critical manner.